PHILOSOPHIC ASPECTS OF MODERNIZATION, CO-EVOLUTION, QUALITY MANAGEMENT - A. I. Loyko (Наука и техника)
Co-evolution has become the main factor that reveals an individual diversity of the Belarusian culture and economy while highly-technological modernization is the major tool for implementation of the ecological quality management aims.